Exposure to Tobacco Smoke and Markers of Subclinical Atherosclerosis in Children and Adolescents. The STRIP Study. - Kallio, Katariina (fi=Turun yliopisto|en=University of Turku|, 2009)
Background: Measurement of serum cotinine, a major metabolite of nicotine, provides a valid marker for quantifying exposure to tobacco smoke. Exposure to tobacco smoke causes vascular damage by multiple mechanisms, and it has been acknowledged as a risk factor for atherosclerosis. Multifactorial atherosclerosis begins in childhood, but the relationship between exposure to tobacco smoke and arterial changes related to early atherosclerosis have not been studied in children. Aims: The aim of the present study was to evaluate exposure to tobacco smoke with a biomarker, serum cotinine concentration, and its associations with markers of subclinical atherosclerosis and lipid profile in school-aged children and adolescents. Subjects and Methods: Serum cotinine concentration was measured using a gas chromatographic method annually between the ages 8 and 13 years in 538-625 children participating since infancy in a randomized, prospective atherosclerosis prevention trial STRIP (Special Turku coronary Risk factor Intervention Project). Conventional atherosclerosis risk factors were measured repeatedly. Vascular ultrasound studies were performed among 402 healthy 11-year-old children and among 494 adolescents aged 13 years. Results: According to serum cotinine measurements, a notable number of the school aged children and adolescents were exposed to tobacco smoke, but the exposure levels were only moderate. Exposure to tobacco smoke was associated with decreased endothelial function as measured with flow-mediated dilation of the brachial artery, decreased elasticity of the aorta, and increased carotid and aortic intima-media thickness. Longitudinal exposure to tobacco smoke was also related with increased apolipoprotein B and triglyceride levels in 13-year-old adolescents, whose body mass index and nutrient intakes did not differ. Conclusions: These findings suggest that exposure to tobacco smoke in childhood may play a significant role in the development of early atherosclerosis. Key Words: arterial elasticity, atherosclerosis, children, cotinine, endothelial function, environmental tobacco smoke, intima-media thickness, risk factors, ultrasound